Uncovering proteome variations and concomitant quality changes of different drying methods Cordyceps sinensis by 4D-DIA structural proteomics - Xiao, Mengjun; Tang, Chuyu; Wang, Tao; He, Min; Li, Yuling; Li, Xiuzhang (Frontiers in Nutrition, 2025)
IntroductionCordyceps sinensis is a fungus, serves dual purposes as both a medicinal herb and a food source. Due to its high water content, fresh Cordyceps sinensis is difficult to preserve, necessitating the drying necessary to process Cordyceps sinensis.MethodsUsing 4D-DIA proteomics, researchers analyzed the proteome profiles of fresh Cordyceps sinensis (CK) under three different drying conditions: vacuum freeze-drying (FD), oven-drying (OD), and air-drying (AD). In addition, it was found that the protein and free sulfhydryl content of Cordyceps sinensis decreased significantly and the disulfide bond content increased after different drying methods.Results and discussionA total of 3762 proteins were identified, showing variations between groups and high protein content. In the control groups consisting of fresh Cordyceps sinensis samples and the three drying methods, FD. vs CK exhibited the fewest differentially abundant proteins, with the majority being upregulated. On the other hand, CK vs OD displayed the greatest amount of distinct proteins, with a significant rise in both up-regulated and down-regulated proteins. Analysis of KEGG indicated that the distinct proteins were predominantly concentrated in pathways like the ribosome, synthesis of coenzymes, and metabolism of amino sugar and nucleotide sugar. Notably, there was a significant overlap between ribosome and ribosome biogenesis in eukaryotes pathways. The process of drying Cordyceps sinensis resulted in a significant upregulation of the expression of proteins linked to various metabolic pathways. This observation suggests that the drying treatment might activate or enhance certain biochemical processes within the organism, potentially influencing its overall metabolic activity. This finding highlights the importance of post-harvest dry methods on the biochemical properties of Cordyceps sinensis, which could have implications for its nutritional and medicinal value.This study provides a theoretical basis for the realization of Cordyceps sinensis resource utilization and storage methods, and provides theoretical support for guaranteeing the sustainable development of Cordyceps sinensis resources.